2011
DOI: 10.1007/s11046-011-9501-z
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Scalp Black Dot Ringworm Caused by Trichophyton tonsurans Among Contact Sports Players

Abstract: We describe here two patients with tinea corporis exhibiting black dot ringworm (BDR). A cluster of black dots was observed on the extensor surfaces of the extremities of two rather hairy male patients, a 15-year-old judo practitioner and a 26-year-old combined martial arts fighter, during treatment of tinea corporis with topical antimycotics. Direct KOH examination showed that the black dots were composed of degenerated hair with numerous arthroconidia and were indistinguishable from BDR of tinea capitis. Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…tonsurans in 14 wrestlers in Adana, Turkey. The molecular type EvSO 3 (which corresponds to non‐transcribed spacer 1) has been previously described in the USA, Canada and Japan 10,22,23 . Notably, we reported that in both a clonal outbreak 10 and a longitudinal study, 19 the most common clinical presentation of T .…”
Section: Discussionmentioning
confidence: 63%
“…tonsurans in 14 wrestlers in Adana, Turkey. The molecular type EvSO 3 (which corresponds to non‐transcribed spacer 1) has been previously described in the USA, Canada and Japan 10,22,23 . Notably, we reported that in both a clonal outbreak 10 and a longitudinal study, 19 the most common clinical presentation of T .…”
Section: Discussionmentioning
confidence: 63%
“…They substitute hair cells almost entirely and are visible inside the hair. Sometimes, it leads to hair breaking off at or below the mouth of the follicle, leaving the residual part inside the follicle, which gives an impression of black dots on a smooth, bald background and thus a black-dot ringworm” appearance [ 3 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this particular region, TG can be divided into three major clinical types [ 6 ]: Black-dot ringworm type—a result of a hair invasion ( endothrix ) [ 37 ]. In dermoscopic assessment, they can be found as a “comma-shaped” hair—a short hair with homogenous pigmentation and thickness [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations